Potential human health risks of toxic/harmful elements by consumption of Pseudevernia furfuracea - Topal, Murat; Arslan Topal, E. Isil; Obek, Erdal; Aslan, Ali (Taylor & Francis Ltd, 2022)
The potential human health risks of some toxic/harmful elements related to the consumption of Pseudevernia furfuracea (L.) Zopf. were investigated. The toxic/harmful elements (cadmium (Cd), chromium (Cr), copper (Cu), lead (Pb), manganese (Mn), nickel (Ni), and zinc (Zn)) were determined in P. furfuracea. According to the analysis result, the maximum (max.) toxic/harmful element value was 62 +/- 3.1 mg/kg for Mn and minimum (min.) value was 0.19 +/- 0.01 mg/kg for Cd. The estimated daily exposure doses (EDEXDs) for men, women and children were dietary (bread) > dietary (tea) > dermal. For dietary (bread) and dietary (tea) non-carcinogenic (HQ) risk was children > women > men. For dermal, HQ risk was women > children > men. Hazard index (HI) value for men was >1 for Cr. HI value for men was 1.36 for Cr. HI value for women was >1 for Cr and Mn. HI values for women were 1.54 for Cr and 1.01 for Mn. Also, the HI value for children was >1 for Cr, Mn, and Pb. HI values for children were 3.44 for Cr, 2.24 for Mn, and 1.66 for Pb. This situation showed that there was a non-carcinogenic risk. Carcinogenic risk values were dietary (bread) > dietary (tea) > dermal. The total max. carcinogenic value was 1.97E-03 for Cr while the total min. carcinogenic value was 1.31E-05 for Pb. As a result, it has been determined that there may be a risk of cancer due to the consumption of lichen as bread and this situation may adversely affect human health.
Keywords: Carcinogenic; food; hazard; lichen; non-carcinogenic